Aesthetics of Futurism: Lu Yang's Art and an Organological Redefinition of the Human in the Planetary Age. Issue 1 (1st June 2022) - Ren, Hai
Abstract: Studying artworks on the human body and the brain, as exemplified by Lu Yang's work, enables a new perspective in the debates over the redefinitions of the human, whether anthropocenic redefinitions of the human (in the scholarships of the Anthropocene, posthumanism, new materialism, and speculative realism) or a technoscientific redefinition of the human (in the scholarships of technological transformations). Not only does Lu Yang question the defining properties of the humanness but the artist also creates an organological form of the human. This organological perspective enables an aesthetics of futurism based on both a nonreproductive kinship between the human and the nonhuman, and a new regime of the future grounded in the habitability of the human as a more-than-human agent in the planetary age.